THE PROLIFERATIVE PROFILE OF THE RHOMBENCEPHALICDEMILUNE IN THE DEVELOPING RAT CEREBELLUM: A QUANTITATIVE HISTOCHEMICAL STUDY (Iraqi Journal of Medical Sciences, 2016)
Background:Studies have shown that the cerebellum develops within the dorsal metencephalon creating a rhombencephalicdemilune (RD) which represents the formation site of the cerebellum granular cells progenitors. These studies used different histological techniques but all have provided qualitative information regarding the biosynthesis and cell mitosis at the RD.Objective:Quantifying the proliferative activity of the cellsat the RD during the embryonic period.Methods: Six age groups from day 16 to day 21 albino rat embryos Rattusrattusnorvegicus were investigated with Ag-NOR staining technique to quantify cell proliferation.Results:There wasa statistically significant difference (p
Keywords: Rhombencephalicdemilune; Rat; Developing Cerebellum; AgNOR; Quantitative; Histochemistry